HAPPY : A MOBILE APPLICATION TO AID MENTAL HEALTH - Thiyagarajan, Harvint Raj (IRC, 2020)
Mental health is something that should not be taken into light consideration because it affects people without know their age, gender or race. Anyone in this world is capable of succumbing to mental health issues. Thus, a mobile application idea is proposed in this project which mainly aimed for students with mental health issues. This application’s intention is to provide a platform for these people to find the understanding off the mental issues that they are facing, and to find ways to learn on how to cope with them. On the other hand, people with mental health issues are able to self-diagnose and find themselves a counselor or a psychologist if their mental health issues get overboard. This idea was proposed and acknowledged by The University’s psychological and counseling unit mainly because the number of students in Universiti Teknologi Petronas that has mental health issues has increased over the years. Hence, this article provides an overall picture of how Happy could be a way to overcome mental health issues among students in the University. Furthermore, a great amount of literature related to this report was gathered in order to justify why this project is necessary. The development of this project is planned to be constructed using the agile methodology which is well known in the mobile application development projects. By the end of this project's development, I hope happy could play a part in overcoming a person's mental health issues.